Tingkat Pengetahuan Penggunaan Kosmetik pada Akne Vulgaris serta Sikap dan Perilaku Penggunaan Kosmetik pada Mahasiswa Fakultas Kedokteran - Sabrinna R. N. Hanumningtyas; Ferra O. Mawu; Nurdjannah J. Niode (Medical Scope Journal, 2024)
Abstract: Some cosmetics contain risky ingredients for the skin, especially for those with sensitive skin or acne. This study aimed to obtain the level of knowledge, attitude, and behavior towards cosmetics use in acne vulgaris (AV) among medical students. This was a descriptive categorial with a cross sectional design using primary data in the form of questionnaires. Respondents were students of Medical Faculty, Universitas Sam Ratulangi, Manado. The results showed that the level of knowledge of the cosmetics use in AV was in the moderate category (53.6%). The attitude of cosmetic use in the poor category was 100%. The behaviors of cosmetic use were, as follows: face cleaning twice a day (71.5%), using one type of facial cleanser (43.6%), using one facial cleansing device (71.5%), always using facial cream (36.9%), always using sunscreen (46.9%), and female respondents who used solid powder (41.8%). In conclusion, the level of knowledge of medical students at Universitas Sam Ratulangi was in moderate category, meanwhile the attitude was in poor category. Furthermore, the majority of students exhibited the behavior of cleansing their faces twice daily, using a singular type of facial cleanser and cleansing device. Additionally, most students consistently applied facial cream and sunscreen, while a significant portion of female respondents using compact powder. Keywords: level of knowledge; attitude; behavior; cosmetics; medical students    Abstrak: Beberapa jenis kosmetik mengandung bahan berisiko bagi kulit, terutama untuk yang berkulit sensitif atau berjerawat. Penelitian ini bertujuan untuk mengetahui tingkat pengetahuan penggunaan kosmetik pada acne vulgaris (AV) serta sikap dan perilaku penggunaan kosmetik pada mahasiswa Fakultas Kedokteran (FK). Jenis penelitian ialah deskriptif kategorik dengan desain potong lintang menggunakan kuesioner. Responden penelitian ialah mahasiswa FK Universitas Sam Ratulangi (Unsrat). Hasil penelitian memperlihatkan tingkat pengetahuan penggunaan kosmetik pada AV berada dalam kategori cukup sebesar 53,6%. Sikap penggunaan kosmetik responden berada dalam kategori kurang sebesar 100%. Perilaku penggunaan kosmetik responden dalam membersihkan wajah 2x/hari (71,5%), menggunakan satu jenis pembersih wajah (43,6%), menggunakan satu perangkat pembersih wajah (71,5%), selalu menggunakan krim wajah (36,9%), selalu menggunakan tabir surya (46,9%), dan responden perempuan yang menggunakan bedak padat (41,8%). Simpulan penelitian ini ialah tingkat pengetahuan mahasiswa FK Unsrat ialah cukup, sikap mahasiswa dalam penggunaan kosmetik ialah kurang, dan perilaku mahasiswa mayoritas membersihkan wajah dua kali sehari, menggunakan satu jenis pembersih dan perangkat pembersih wajah. Sebagian besar mahasiswa selalu menggunakan krim wajah dan tabir surya, serta sebagian besar responden perempuan menggunakan bedak padat.   Kata kunci:  tingkat pengetahuan; sikap; perilaku; kosmetik; mahasiswa fakultas kedokteran